Factors that influence the English Language teaching-learning process in Ecuadorian private high schools - Sarmiento Pesántez, Mercedes Magdalena (2014)
This research work intends to explain factors that influence the English language teaching-learning process in Ecuadorian private schools. The research was done in the province of Cañar in the city of Azogues, and in the province of Azuay in the city of Cuenca. Fifteen teachers and 15 students were selected as a sample. For this research work, the qualitative and quantitative approaches were used. The qualitative methods was used for the narrative data in all of the process; and the quantitative research was used to obtain measurable and observable data on variables. One main factor that affects the quality of English in language teaching-learning process in Ecuadorian private high schools is the number of students. Teachers require the use of teaching resources and methods from which the Communicative Language Teaching Method is mostly applied.